The predictive value of uric acid/albumin ratio for no-reflow/slow-flow in patients after PCI for acute non-ST segment elevation myocardial infarction - GONG Junrong, LI Yafei, DAI He, ZHU Fuyu, CHEN Wenting (Zhongguo linchuang yanjiu)
Objective： To investigate the correlation between the uric acid/albumin ratio (UAR) and the occurrence of no-reflow/slow-flow after percutaneous coronary intervention (PCI) in patients with acute non-ST segment elevation myocardial infarction (NSTEMI), and to analyze its predictive value. Methods： A retrospective analysis was conducted on the data of 324 NSTEMI patients who underwent PCI within 24 hours of admission at Suzhou Hospital Affiliated to Nanjing Medical University between March 2021 and February 2024. The thrombolysis in myocardial infarction (TIMI) flow score was used to describe blood flow. A TIMI score of 0-2 was categorized as the no-reflow/slow-flow group (39 cases), and a TIMI score of 3 as the normal flow group (285 cases). Baseline characteristics and lesion characteristics of patients with normal flow and patients with no-reflow/slow-flow were compared.Multivariate logistic regression was used to analyze the independent factors affecting the occurrence of no-reflow/slow-flow in NSTEMI patients.ROC curve was plotted to analyze the predictive value of UAR for the occurrence of no-reflow/slow-flow. Results： Multivariate logistic analysis showed that UAR, urea and SYNTAX score were independent influencing factors of no-reflow/slow-flow occurrence (P＜0.05). The ROC curve showed that the area under the curve (AUC) for UAR was 0.869, significantly higher than that for urea (AUC=0.676) and SYNTAX score (AUC=0.860). Conclusion： UAR is an independent predictor of no-reflow/slow-flow after PCI in NSTEMI patients. Clinically, UAR can be used to predict the risk of no-reflow/slow-flow in NSTEMI patients after PCI.